2022
DOI: 10.1101/2022.07.14.500042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fc effector activity and neutralization against SARS-CoV-2 BA.4 is compromised in convalescent sera, regardless of the infecting variant

Abstract: The SARS-CoV-2 Omicron BA.1 variant, which exhibits high level neutralization resistance, has since evolved into several sub-lineages including BA.4 and BA.5, which have dominated the fifth wave of infection in South Africa. Here we assessed the sensitivity of BA.4 to neutralization and antibody dependent cellular cytotoxicity (ADCC) in convalescent donors infected with four previous variants of SARS-CoV-2, as well as in post-vaccination breakthrough infections (BTIs) caused by Delta or BA.1. We confirm that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 32 publications
(63 reference statements)
4
12
0
Order By: Relevance
“…In contrast, they were unable to neutralize BA.1, in agreement with previous reports (42,57,75). This observation somehow mirrors the restricted cross-neutralizing ability of BA.1elicited antibodies against pre-Omicron and other Omicron lineages (3,20,30,42,50,63,66,73,(75)(76)(77)89), and highlights that BA.1 is antigenically very distant from all other VOCs and triggers strongly imprinted immune responses. Accordingly one study found that BA.1 booster triggers the activation of naïve B-cells rather than memory B-cells (74), while others record a small proportion of naïve B-cell activation (2,63,67,87).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In contrast, they were unable to neutralize BA.1, in agreement with previous reports (42,57,75). This observation somehow mirrors the restricted cross-neutralizing ability of BA.1elicited antibodies against pre-Omicron and other Omicron lineages (3,20,30,42,50,63,66,73,(75)(76)(77)89), and highlights that BA.1 is antigenically very distant from all other VOCs and triggers strongly imprinted immune responses. Accordingly one study found that BA.1 booster triggers the activation of naïve B-cells rather than memory B-cells (74), while others record a small proportion of naïve B-cell activation (2,63,67,87).…”
Section: Discussionsupporting
confidence: 91%
“…Hybrid immunity conferred by vaccination and infection together was reported to be superior to immunity elicited by infection or vaccination alone (3,20,37,38,65,66,70,73,76,(82)(83)(84)(85). We therefore further investigated the susceptibility of the four Omicron sublineages to sera from 16 Despite distinct neutralization profiles, all but one BTI sera had antibodies against S, the RBD and the NTD (Fig 3M).…”
Section: Breakthrough Infection Sera Have Distinct Neutralization Pro...mentioning
confidence: 98%
See 3 more Smart Citations